2012
DOI: 10.1021/ie2027298
|View full text |Cite
|
Sign up to set email alerts
|

Exergy Analysis of Biomass Drying Based on Self-Heat Recuperation Technology and Its Application to Industry: a Simulation and Experimental Study

Abstract: An energy-saving process for biomass drying was proposed to improve the overall energy efficiency by using selfheat recuperation technology for future industrial use. Energy analysis based on the simulation results showed that the primary energy consumption and CO 2 emission in the proposed process can be decreased to 74% and 36% of that of the conventional heat recovery dryer, respectively. Moreover, exergy analysis was conducted to clarify exergy losses in the proposed drying process, and further energy-savi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Biomass waste has a potential to substitute fossil fuels, therefore it is attractive to use biomass waste as feedstock for energy production because of its high carbon and hydrogen content in addition to a variety of chemical compounds [4]. However, its physical properties such as low energy density and high moisture content result in high logistic costs and reduced thermal efficiency of energy conversion [5]. The development of efficient conversion technologies of biomass to be efficient is the challenge so as to compete economically with fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass waste has a potential to substitute fossil fuels, therefore it is attractive to use biomass waste as feedstock for energy production because of its high carbon and hydrogen content in addition to a variety of chemical compounds [4]. However, its physical properties such as low energy density and high moisture content result in high logistic costs and reduced thermal efficiency of energy conversion [5]. The development of efficient conversion technologies of biomass to be efficient is the challenge so as to compete economically with fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…(4) Based on the data in the manufacturer's catalog, the adiabatic efficiency of the fluidized gas blower was 0.60, while that of the steam compression blower was 0.56. (5) The adiabatic efficiency of the compressor in the VRC was set to 0.80. (6) The thermodynamic calculations were performed using the IDEAL method.…”
Section: Simulation Conditionsmentioning
confidence: 99%
“…Liu et al conducted exergy analysis on the drying systems and found a large exergy loss occurred due to the existence of air. A more energy-saving potential was predicted with condensable gas as the drying medium [5]. Fig.…”
Section: Introductionmentioning
confidence: 97%
“…Notably, biomass materials are generally rich in oxygen content, possess low bulk density, and have relatively low calorific heating values. Compared to coal, biomass has a lower thermal content, higher moisture content, lower bulk density, and its physical form is neither homogeneous nor free-flowing, which usually makes biomass unusable without further processing [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Soluble and Deposit are extracted products, while Residue is the unextracted product. The method is able to upgrade low-rank coal and biomass through the selective removal of oxygen functional groups in the form of H 2 O or CO 2 [10,16,19]. The Soluble fraction has a high carbon content (81-83.3 wt.%), a low oxygen content, and is almost completely free from ash [16].…”
Section: Introductionmentioning
confidence: 99%